The impacts of Chinese FDI on domestic investment and economic growth for Africa - Miao Miao; Dinkneh Gebre Borojo; Yushi Jiang; Tigist Abebe Desalegn (Cogent Business & Management, 2021)
This study examines the role of domestic governance quality on the relationship between Chinese foreign direct investment (FDI), domestic investment, and African countries' economic growth. The study utilized a larger dataset of Chinese FDI to 44 African countries applying the two-step system GMM estimation method for 2003-2017. This study's findings reveal that Chinese FDI's impact on economic growth is conditional to improving African countries' aggregate and each component of individual governance indicators used to represent the countries' institutional quality. The impact of Chinese FDI on African countries' domestic investment is robustly positive. Besides, improvement in the governance environment stimulates the effect of Chinese FDI on domestic investment. More specifically, control of corruption, government effectiveness, and voice and accountability have mediating roles in the nexus of Chinese FDI and African countries' domestic investment. Thus, African countries aiming to attract Chinese FDI and promote their economic growth and domestic investment need to improve governance quality.
Keywords: F35; F41; 650; FDI; domestic investment; economic growth; the two-step system GMM estimator; China-Africa